Closed-form expressions for improved impact resistant design of reinforced concrete beams. (February 2021) - Yong, Arnold C.Y.; Lam, Nelson T.K.; Menegon, Scott J.
Abstract: To facilitate the design of structural elements that are vulnerable to collision hazards, simple closed-form expressions have been stipulated in major codes of practice for quantifying the associated design impact actions. It is revealed in this article that the peak deflections from impact loading predicted using the closed-form expressions found in many of the major codes of practice around the world are in gross disagreement with observations from experimental testing in literature. This observation was following the review and assessment of the test results recorded from 68 dynamic experiments on reinforced concrete (RC) beams. The articles presenting these test results have not proposed new analytical models for guiding predictions nor have evaluated any existing analytical models. To fill this knowledge gap, this article proposes new closed-form expressions that were developed using displacement-based design principles and validated against 68 test results from literature, which showed the expressions provide accurate predictions of the deflection demand on RC beams subject to impact actions.